Mairil and Nyempet as Child Sexual Violence in Pesantren: Contradictions of Traditional Norms, Religion, and Criminal Law Policy in Indonesia - Mohamad Tohari; Iqbal Kamalludin; Jarot Jati Bagus Suseno; Achmad Jauhari Umar; Bunga Desyana Pratami (Universitas Negeri Semarang, 2024)
Pesantren, Islamic educational institutions in Indonesia, traditionally provide dormitories for santri, students dedicated to religious studies from childhood through adolescence. However, adolescence often coincides with heightened curiosity about sexuality, leading to behaviors like